Reconstitution of a Calcium Pump Using Defined Membrane Components - Warren, G. B. (1974)
A (Mg(2+) + Ca(2+))ATPase (ATP phosphohydrolase, EC 3.6.1.3) has been purified from sarcoplasmic reticulum using a single step centrifugation procedure. The preparation is >95% pure by weight and contains only 25-30% of the lipid associated with the enzyme in native sarcoplasmic reticulum. The purified enzyme is unable to accumulate Ca(2+). Using a sedimentation-substitution technique, >98% of the lipid associated with the purified enzyme can be replaced by dioleoyl lecithin without grossly affecting the ATPase activity of the enzyme. The Ca(2+) pump can be restored to this dioleoyl lecithin-substituted enzyme by addition of excess sarcoplasmic reticulum lipids in the presence of cholate. Removal of the cholate by dialysis generates a system which accumulates Ca(2+) at a rate and to a level comparable to native sarcoplasmic reticulum. Significant reconstitution of the Ca(2+) pump can also be achieved using excess dioleoyl lecithin, but since the full expression of the capacity to accumulate Ca(2+) requires the presence of oxalate, these vesicles would appear to be more leaky than those reconstituted with an excess of sarcoplasmic reticulum lipids. Of about 90 lipid molecules which are associated with one molecule of ATPase in native sarcoplasmic reticulum, an average of less than one lipid molecule remains in these reconstituted systems. We have therefore achieved a fully functional Ca(2+) pump containing essentially a single protein and exogenous lipid.